2012
DOI: 10.1128/jvi.01208-12
|View full text |Cite|
|
Sign up to set email alerts
|

Norovirus RNA Synthesis Is Modulated by an Interaction between the Viral RNA-Dependent RNA Polymerase and the Major Capsid Protein, VP1

Abstract: Using a cell-based assay for RNA synthesis by the RNA-dependent RNA polymerase (RdRp) of noroviruses, we previously observed that VP1, the major structural protein of the human GII.4 norovirus, enhanced the GII.4 RdRp activity but not that of the related murine norovirus (MNV) or other unrelated RNA viruses (C. V. Subba-Reddy, I. Goodfellow, and C. C. Kao, J. Virol. 85:13027–13037, 2011). Here, we examine the mechanism of VP1 enhancement of RdRp activity and the mechanism of mouse norovirus replication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 50 publications
0
58
0
Order By: Relevance
“…Recently, Subba-Reddy et al (43) showed that VP1 directly interacts with the RNA-dependent RNA polymerase (RdRp) through its S domain and exhibits a concentration-dependent regulatory activity on RNA translation and RNA synthesis. These studies suggest that after virus entry into cells and capsid disassembly, released VP1 enhances RdRp activity, and the VP1 stimulatory effect continues during the replication cycle concomitant with increased production of VP1.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Subba-Reddy et al (43) showed that VP1 directly interacts with the RNA-dependent RNA polymerase (RdRp) through its S domain and exhibits a concentration-dependent regulatory activity on RNA translation and RNA synthesis. These studies suggest that after virus entry into cells and capsid disassembly, released VP1 enhances RdRp activity, and the VP1 stimulatory effect continues during the replication cycle concomitant with increased production of VP1.…”
Section: Discussionmentioning
confidence: 99%
“…In this assay, the RNAs synthesized by the MNV RdRp serve as agonists for the innate immune receptor RIG-I, activation of which leads to firefly luciferase reporter expression from a beta interferon promoter (45). Importantly, coexpression of the wild-type MNV VPg with the MNV polymerase was found to increase luciferase production by about 40 to 50% (71).…”
Section: H-mentioning
confidence: 99%
“…High-throughput DNA sequencing was performed using the Illumina MiSeq system. CLIP-Seq was performed as described previously (17,18). Analyses of MiSeq reads were performed using the Galaxy User Interface.…”
Section: Methodsmentioning
confidence: 99%
“…Amplifications were performed with an initial incubation at 10 min at 95°C, followed by up to 45 cycles of 15 s at 95°C, 20 s at 60°C, and 60 s at 72°C. The mRNA levels were normalized to GAPDH mRNA level, and the changes were compared with the mock-transfected control as previously reported (18). MiR-122 levels were quantified using the protocol of Livak and Schmittgen (19).…”
Section: Sirna Knockdown Of Hnrnp K and Quantitative Reverse Transcrimentioning
confidence: 99%
See 1 more Smart Citation